To find f(-4), we substitute x = -4 into the equation f(x) = -4x - 5:
f(-4) = -4(-4) - 5
Simplifying this expression:
f(-4) = 16 - 5
f(-4) = 11
Now, to find f(-4f(-4)), we substitute -4f(-4) into the equation f(x) = -4x - 5:
f(-4f(-4)) = -4(-4f(-4)) - 5
Substituting the value we found for f(-4) earlier:
f(-4f(-4)) = -4(-4(11)) - 5
Simplifying this expression:
f(-4f(-4)) = -4(-44) - 5
f(-4f(-4)) = 176 - 5
f(-4f(-4)) = 171
Given f, of, x, equals, minus, 4, x, minus, 5f(x)=−4x−5, find f, of, minus, 4f(−4)
1 answer